Cartography and geopolitics in the Arctic region - Jeppe Strandsbjerg (Danish Institute for International Studies (DIIS), 2010)
This paper discusses the relationship between geography and politics; and more specifically, the relationship between sovereign claims and cartography. I introduce the term 'cartopolitics' to describe a particular way of making space real and corresponding with politics that defines contemporary bordering practices in the Arctic region. The paper argues that too often boundary studies assume that socio-political space arises as a result of boundary practices. In contrast, this paper proceeds from a notion that space should precede boundaries in the analysis because, unless space is taken as a natural given and constant background, its 'construction' conditions how boundaries can be established in the first place. In sequence, I argue how the United Nations Convention on Law of the Sea builds on - and requires - a particular spatiality epitomised by so-called modern cartography. This has implications for the way in which sovereignty over space is transferred from a political to a scientific domain, and essentially, it tends to mask the constructed nature of the spatiality given objectivity through the law of the sea.
Keywords: 330